If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8x + 6 = 7x + -1 Reorder the terms: 6 + 3x + -8x = 7x + -1 Combine like terms: 3x + -8x = -5x 6 + -5x = 7x + -1 Reorder the terms: 6 + -5x = -1 + 7x Solving 6 + -5x = -1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + -5x + -7x = -1 + 7x + -7x Combine like terms: -5x + -7x = -12x 6 + -12x = -1 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -12x = -1 + 0 6 + -12x = -1 Add '-6' to each side of the equation. 6 + -6 + -12x = -1 + -6 Combine like terms: 6 + -6 = 0 0 + -12x = -1 + -6 -12x = -1 + -6 Combine like terms: -1 + -6 = -7 -12x = -7 Divide each side by '-12'. x = 0.5833333333 Simplifying x = 0.5833333333
| 10+10=(208)+10 | | 2n+6=-10 | | 3.25-y=-0.75 | | Z=4+7i | | 4x+(x-3)6=92 | | 3.25-y=0.75 | | F(x)=-x^2+3x-2 | | 12-(3m+3)=2+3m-11 | | 5A+2(3A-5)=1+5(A+2)-A+3(3-4) | | 6x+2x-4=3x-3+12 | | 4t+35=10t-37 | | 2b+4=-18+-9 | | 2y+x-3=0 | | 8m+4=8m | | (x-380)(x^2+2)=0 | | 2x+x+y=180 | | 4x+(4x-3)6=92 | | 2(x-5)=7x+6x | | x+30=4x+9 | | 10=60-5x | | 8-5X-10X+6= | | 3w=w-30 | | 2x-(-4)+3=2x-1 | | 3x-4(9-2y)+5x=2y+3(x-y) | | 2c-6=2(c-3) | | 3x+4(2x-7)+12=4+5(3x+4) | | a+39=5a-37 | | 3x^2-130x-1000=0 | | 5m+1m=100 | | 2x^3+5x-9=0 | | (x+1)(4-3i)(4+3i)=0 | | 17=-5(3+w)+w |